Implementasi Manajemen Pendidikan dalam Meningkatkan Mutu Pendidikan : Penelitian - Mamentu , Meike Drita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the implementation of educational management in improving education quality through four main indicators, namely educational planning, organizing, implementation, and supervision. The research employs a qualitative approach using in-depth interview techniques with five informants consisting of the principal, vice principal, senior teacher, administrative staff, and school committee. The data were analyzed through data reduction, data display, and conclusion drawing. The results show that educational planning has been systematically arranged and involves all stakeholders, although there are still obstacles related to the consistency of program implementation. The organization of education runs quite effectively with a clear division of tasks, but coordination among parties is not yet optimal. In terms of educational implementation, teachers have applied various learning models and utilized technology, although some supporting facilities remain inadequate. Educational supervision is carried out routinely through supervision and evaluation; however, the follow-up actions for improvements have not been maximized. Overall, the implementation of educational management has contributed positively to improving education quality, although strengthening is still needed in aspects of coordination, facilities, and follow-up systems for supervisory results.